FLIR/INS/RA Integrated Landing Guidance for Landing on Aircraft Carrier. (20th May 2015) - Ding, Zhenxing; Li, Kui; Meng, Yue; Wang, Lingcao
This paper presents a FLIR/INS/RA integrated landing guidance method to provide information of aircraft states and carrier dynamics for fixed-wing aircraft landing on the aircraft carrier in low-visibility weather and high sea states. The method utilizes the Forward-Looking Infrared (FLIR) system, the Inertial Navigation System (INS), and the Radio Altimeter (RA) as sensors, to track infrared cooperated targets on the aircraft carrier. Several algorithms like the Newton iterative algorithm, the Kalman Filter (KF), and the Wavelet Transform (WT) are employed to compute real-time and high-precision estimates of the aircraft states (runway-related position, attitude, and velocity) and the carrier dynamics (pitch, roll, and heave). A simulation experiment is conducted and shows satisfactory results for the aircraft carrier landing guidance.